Integrating Deep Learning-Oriented Instruction in Indonesian EFL Classrooms: Teachers’ Perspectives - Syilla, Salsabilla; Dewi, Utami; Dalimunthe, Muhammad (Jurnal Ilmiah Religiosity Entity Humanity (JIREH), 2026)
This study examines English teachers’ perspectives on the integration of deep learning-oriented instruction in Indonesian English as a Foreign Language (EFL) classrooms. Drawing on a qualitative research design, the study involved three senior high school English teachers from a public school in North Aceh, Indonesia. The findings indicate that teachers conceptualize deep learning as an approach that emphasizes critical thinking, inquiry, collaboration, problem-solving, and reflective learning rather than surface-level knowledge acquisition. In classroom practice, deep learning was enacted through inquiry-based activities, problem-based tasks, collaborative learning, and reflective practices that encouraged meaningful language use and student engagement. Teachers perceived deep learning as beneficial for enhancing learner autonomy, communicative competence, and higher-order thinking skills. However, several challenges were identified, including limited instructional time, heterogeneous student proficiency, and resource constraints. To address these challenges, teachers adopted adaptive strategies such as scaffolding, differentiated instruction, and flexible task design.